Optimalisasi Penyediaan Fasilitas Umum melalui Kompetensi Mitigasi Bencana pada Institusi Publik - Meutia, Intan Fitri; Muflihah, Lilih; Kagungan, Dian; Sutiyoso, Bambang Utoyo; Assalam, Muhammad Shafwan; Sujadmiko, Bayu (Jurnal Pengabdian Dharma Wacana, 2024)
Awareness of the importance of disaster mitigation and responsiveness to disasters, especially fires and earthquakes, aims to minimize the impact that these disasters can cause. Improving the skills of the entire academic community of the Faculty of Social and Political Sciences in prevention management, handling and responsiveness to fire and natural disasters is an important need to do. The simulations that will be carried out through community service activities are targeted at increasing individual and collective knowledge and abilities, a spirit of togetherness, collective awareness and cooperation in disaster prevention and response. This activity is of course a form of partnership between the Faculty of Social and Political Sciences and BPBD Bandar Lampung City. The establishment of ongoing cooperation and synergy between the two agencies which will be used as a reference for other agencies and faculties to increase collective awareness. The target of this activity is the entire academic community consisting of Educators and Education, Students and other faculty members of Universitas Lampung.